



 
Hi Jordan, The subject line of the email you sent indicated that you want to expand this expression. I am going to illustrate using a different expression.
First of all I am going to ignore the 5 and expand $(x + 2)( x  5).$ This I would do using the distributive law. \[(x + 2)( x  5) = x(x  5) + 2(x  5).\] Expand and simplifying yields \[x(x  5) + 2(x  5) = x^2  5 x + 2 x + 2 \times 5 = x^2  3x  10.\] Now we need to include the 5 we ignored so my solution is \[5(x + 2)( x  5) = 5(x^2  3x  10) = 5x^2  15x  50.\] Now try your problem,  


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences. 